Life Cycle Assessment (LCA) of the Wastewater Treatment Plant of a Lead-Acid Battery Manufacturing Industry - Yosef Barita Sar Manik; Surya Nita Zebua (JST (Jurnal Sains dan Teknologi), 2025)
Liquid waste generated from lead–acid battery production contains hazardous pollutants and requires intensive treatment, which may lead to significant environmental impacts. This study aims to analyze the potential environmental impacts and to examine the contributing factors associated with the operation of the wastewater treatment plant (WWTP). The research adopts an exploratory approach with a site-specific focus, using the WWTP of PT XYZ as the study object. Data were collected through on-site measurements, operational monitoring reports, and company records, which served as secondary data sources. Data analysis was conducted based on the four main stages of Life Cycle Assessment (LCA). The main findings indicate that electricity consumption and the use of sodium hydroxide (NaOH) are the primary contributors to the potential environmental impacts of WWTP operations. The study concludes that the environmental hotspots within the WWTP in the study area are electricity consumption and NaOH usage. Simulation results demonstrate that a combined strategy involving the substitution of NaOH with calcium hydroxide (Ca(OH)₂) and the implementation of solar panels can reduce potential environmental impacts by up to 71.92% compared to the business-as-usual scenario. This study provides practical guidance for lead acid battery manufacturers in reducing the potential environmental impacts of wastewater treatment operations.